D.02 Predictive factors for epilepsy in pediatric patients with Sturge Weber Syndrome. (17th June 2016) - Kaseka, ML; Bitton, JY; Major, P
Abstract : Background: Sturge Weber Syndrome (SWS) patients at risk of epilepsy are often not identified before their first seizure which leads to unnecessary follow up of many patients with facial angioma.Methods: The medical photography database of our institution has been reviewed to identify SWS patients followed between 1993 and 2013. Patients with isolated glaucoma were compared to patients with epilepsy regarding the location of the facial angioma, the presence of asymmetrical background activity on EEG done prior epilepsy onset and cerebral imaging. Logistical regression tests and a p-value of 0.05 were used.Results: 21 patients with SWS have been identified. No significant difference was noted when patients were compared based on the laterality of the lesion (p=0.169), or the location of the facial angioma (p = 0.314 to 0.999). Only 2 epileptic patients had digital EEG done prior the onset of epilepsy and only 2 patients with glaucoma had digital EEG done during their follow up. No significant difference was noted between EEG background activities in the two groups (p= 0.514). The presence of venous drainage anomalies (VDA) predicted (p = 0.004) the onset of epilepsy.Conclusions: Cerebral VDA increases the risk of epilepsy in SWS patients. Since they can be detected at birth, they might guide the management.